ESSENTIAL COMMENTS ON THE CHARACTERISTICS DUE TO THE ORIGIN OF CLINICAL TERMS AND FEATURES OF CLINICAL TERMINOLOGY - Sharipov Bobur Salimovich (Research Focus International Scientific Journal, 2023)
This article discusses the characteristics of Latin clinical terms. It provides information on the formation and interconnection of clinical terms, the place and role of prefixes and suffixes in the formation of terms.